Cross-cultural translation and linguistic validation of the eating motivation survey among older adults in the Chinese context - Wu, Lina; Chen, Xi; Feng, Hui; Cheng, Shouzhen (Frontiers in Nutrition, 2025)
BackgroundDiet quality is a determinant of healthy aging and contributes to reducing the risk of chronic diseases such as cardiovascular disease, diabetes, and cancers, which impose considerable burdens on healthcare systems in China. Despite significant nutritional guidelines, older adults’ adherence to healthy eating remains inadequate. Understanding the determinants is essential for improving their adherence. Eating motivation is a key factor in exploring the reasons behind food choices.MethodsBrislin’s classical translation model was rigorously utilized to translate the Eating Motivation Survey (TEMS) into Chinese, involving forward translation, back translation, and expert consultation by a panel of healthcare and nutrition specialists. Cognitive interviews were conducted for further adaptation to assess clarity, intelligibility, and cultural appropriateness, following the Cognitive Interviewing Reporting Framework (CIRF). After linguistic adaptation, the Chinese version of TEMS was used on eligible older adults to test the reliability and validity.ResultsCognitive interviews conducted with 23 participants over 3 iterative rounds revealed issues with item wording, font size, and layout. Additionally, 249 elderly community residents participated in testing the reliability and validity. A total of 12 items were reworded to adapt the instrument to Chinese culture while maintaining their conceptual objectives. Colloquial words were revised and the formatting was adjusted with 1.5 line spacing and a font size of 14 in SimSun font to enhance readability. Practical examples were added to improve item comprehension, particularly for less-educated respondents. The results indicated that Cronbach’s α coefficient was 0.772, and the split-half coefficient was 0.871.ConclusionThis study successfully adapts TEMS to the Chinese context, providing a reliable and culturally sensitive measure of eating motivations, which is crucial for developing effective dietary interventions to enhance diet quality and promote healthy aging. The study underscores the importance of considering linguistic and cultural nuances in cross-cultural instrument adaptation and offers insights for future studies.